An Econometric Investigation into the Relationship between Boardroom Diversity and Firm Performance. - Henry, Jessica (2018)
Demographic diversity in boardrooms has often been advocated as a means of improving organisational performance through providing a range of different perspectives and ideas. However, there is much debate as to whether there is an economic case for more diverse boards arising from improved financial performance. This study contributes to the limited body of work which examines the relationship between demographic diversity on boards and firm financial performance for UK firms. The empirical analysis uses director and firm level data from 85 FTSE 100 firms from the period 2008 to 2017, employing two measures of diversity within boardrooms: gender diversity and a novel measure, national cultural diversity, The results indicate that both gender and national cultural diversity are not significantly related to either measure of financial performance; Return on Assets or Tobin’s Q. These findings support the view that the negative aspects of diversity may cancel out the perceived benefits. This research also undertakes further analysis on another topical aspect of the gender debate; the gender pay gap. This additional research investigates the extent to which there is a gender pay gap between male and female directors for UK FTSE 100 firms by analysing the determinants of director salaries. The gender pay gap findings reveal that male directors are paid significantly more than females and that being female is negatively associated with salary